Seroprevalence of Toxoplasma gondii in Cattle and Sheep in Isfahan, Iran - Mitra Sadat Deyhimi (International Journal of Epidemiologic Research, 2019)
Background and aims: Toxoplasma gondii is an obligate intracellular parasite which has the potential to infect all warm-blooded animals. Sheep and cattle play a main role in the economy and their infection to T. gondii, besides economic losses, can cause the infection of humans through the consumption of raw meat and other products. In this study, we aimed to survey the prevalence of T. gondii in the livestock in Isfahan, Iran. Methods: A total of 384 samples including 144 sheep and 130 bovine serum samples from Isfahan and 50 sheep and 60 bovine serum samples from Kashan slaughterhouses were tested for the presence of T. gondii antibody using the indirect immunofluorescence method. Results: In general, the antibody was found in 27.31% of sheep and 22.63% of cattle at a dilution of ≥1:200. In detail, 26.15% of bovine and 26.17% of sheep serums from Isfahan and 15% of bovine and 22% of sheep serums from Kashan were seropositive. Conclusion: The study revealed that sheep and cattle can be a significant intermediate host for the spread of the disease in this region (Isfahan province) and the health and livestock authorities in the province should be given priority in improving animal welfare and nutrition.